AN ANALYSIS OF STUDENTS’ SPEAKING ANXIETY FACED BY THE FOURTH SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM OF ENGLISH DEPARTMENT OF UNIVERSITAS NEGERI PADANG - Weni Delfia Mitha; Zul Amri; Don Narius (Universitas Negeri Padang, 2018)
This research was conducted to find out the type and the level of speaking anxiety faced by the forth semester students of English Education Study Program of English Department of Universitas Negeri Padang. This descriptive research used a quantitative descriptive method. The research instruments are questionnaire and interview. The questionnaire used in this research is adapted from the Foreign Language Anxiety Scale (FLCAS) designed by Horwitz. It consists of 33 statements which have three categories as well as communication apprehension, fear of speaking test, and fear of feedback by peers and lecturer. Based on the research analysis, it was found that the level of students’ speaking anxiety is in the middle level with the percentage was 82%. It was significantly different with other levels which had 9% for low level and also 9% for high level. The types faced by the respondents were in the fear of speaking test (44%), communication apprehension (34%), and feedback by peers and lecturer (22%). The dominant typeof speaking anxiety was fear of speaking test. However, after having the depth interview about their speaking anxiety, the research showed that all types of speaking anxiety were in the relationship. Key words: Speaking, Anxiety